Digital Blackface and Its Argumentative Implications - Henning, Tempest M. (Ethical theory and moral practice, 2025)
While much has been written regarding the harms of Digital Blackface, within this paper I argue that Digital Blackface is harmful on an argumentative level, as opposed to merely socio-political. My position is that the usage of Black GIFs/memes should be curtailed by non-Black and non-users of African American Argumentation (AAA). Rather than offering socio-political reasons members of these groups ought not to use Digital Blackface, I utilize the Pragma-Dialectical model of argumentation. My argument hinges on Black GIFs/memes utilized by non-Blacks and non-AAA users violating two Pragma-Dialectical rules: 1 - the starting point rule and 2 - the usage rule.